Методика графічної реконструкції дерев’яної наскельної архітектури (на прикладі пам’яток ІХ–ХVI століть Західного регіону України) - Рожко, Василь Михайлович (Національний університет "Львівська політехніка", 2013)
У роботі сформовано понятійний апарат, визначено складові інформаційної бази та теоретичні засади графічної реконструкції дерев’яної наскельної архітектури. Запропоновано технології фіксації скель зі слідами забудови з використанням лазерного сканування та фотограмметрії; роботи з матеріалами досліджень за допомогою 3D-моделювання, бази даних та геоінформаційної системи. Описано методи аналізу наскельних слідів забудови, способи оцінювання достовірності відтворених елементів, критерії відбору варіантів. Розроблено методику графічної реконструкції дерев’яної наскельної архітектури, що охоплює методи, принципи та послідовність процедур. За описаною методикою проведено дослідження, у тому числі фіксацію, скельного комплексу Камінь (Тустань). Виконано моделювання п’яти будівельних періодів його втраченої дерев’яної забудови. Подано рекомендації щодо використання методики у реставраційній та пам’яткоохоронній діяльності на різного виду об’єктах. В работе сформулирован понятийный аппарат, определены составляющие информационной базы и теоретические основы графической реконструкции деревянной наскальной архитектуры. Предложены технологии фиксации скал со следами застройки с использованием лазерного сканирования и фотограмметрии; работы с материалами исследований с помощью 3D-моделирования, баз данных и геоинформационной системы. Описаны методы анализа наскальных следов застройки, средства оценки достоверности воспроизведённых элементов, критерии отбора вариантов. Разработана методика графической реконструкции деревянной наскальной архитектуры, охватывающая методы, принципы и последовательность процедур. По описанной методике проведено исследования, в том числе фиксация скального комплекса Камень (Тустань). Выполнено моделирование пяти строительных периодов его утраченной деревянной застройки. Даны рекомендации по использованию методики в реставрационной и памятникоохранной деятельности на объектах разного вида. An analysis of log cliffside architecture monuments shows their uniqueness for world architecture history so as little knowledge of them. The only known methods of cliffside arvhitecture investigation are formed by Mykhailo Rozhko. His documentation methods are based on technological level of 1970s, that’s why they should be renewed due to present geodetic and information technologies. It is necessary to work out theoretical basis and clear rules of log cliffside architecture graphical reconstruction. The author forms conceptual apparatus, especially understanding of log cliffside architecture, cliffside traces and their types, graphical reconstruction. Selection criteria between graphical reconstruction versions are three characteristics of perfect result: definiteness, completeness, minuteness. The author formulate five basic principles and four phases of log cliffside architecture graphical reconstruction, so as investigations for each stage. There are six components which form informational basis for graphical reconstruction founded on facts. Those facts can be collected during field monument and adjacent territory research so as from analogs and historic context investigations. Facts contain information about general building features, its structure, separate elements characteristics. The fullest information about lost architecture lays in cliffside traces for log constructions. Proposed documentation metnods are laser scanning and photogrammetry combination. They provide precise and detailed fixing of cliffs and cliffside traces. All research data should be transmitted to and stored as integrated 3D-model, database and geographic information system. Its needed to use building information system technology for lost architecture modelling. The author implemented proposed methods during research and documentation of Kamin’ cliffs (Tustan fortress). Consecution of lost log cliffside architecture modelling has four phases. The author developes evaluation methods for restored elements trustworthiness, defines principles, approaches, modelling levels and expected results. The result of author’s research is a 3D-model of five building periods on Kamin’ cliffs (Tustan fortress). The author formulates clear methods of log cliffside architecture graphical reconstruction which contains theoretical basis, methods, principles and consecution for this kind of architectural research. Proposed methods are compared with previous ones by M. Rozhko. The author worked out recommendations of methods usage for different monuments restoration and preservation.
Методика графической реконструкции деревянной наскальной архитектуры (на примере памятников IX–XVI веков Западного региона Украины)
Methods of Graphical Reconstruction of Log Cliffside Architecture (on Example of 9–13th Centuries Monuments in Western Ukrainian Region)
Keywords: графічна реконструкція; дерев’яна наскельна архітектура; 3D-моделювання; фіксація; лазерне сканування; фотограмметрія; графическая реконструкция; деревянная наскальная архитектура; 3D-моделирование; фиксация; лазерное сканирование; фотограмметрия; graphical reconstruction; log cliffside architecture; 3D-modelling; documentation; laser scanning; photogrammetry